Controle varietal do ácaro-da-necrose Aceria guerreronis em coqueiro (Acari: eryophidae) - Sousa, Suelen Rayane Cardoso (2015)
The coconut mite, Aceria guerreronis Keifer (Acari: Eriophyidae), is a key coconut pest in America, Africa and Asia. Colonies of A. guerreronis develop under the bracts of coconuts, leading to a reduction in fruit size, liquid and solid albumen, and their commercial value. Although the relationship between the coconut mite damage and the reduction in production is known, the interaction between the attack of this pest and varietal susceptibility in productive parameters remains yet to be investigated. Therefore, the present work aimed to evaluate the interaction between six intervarietal hybrids and the coconut mite damage in productive parameters of coconut hybrids for the conditions of the state of Pará. Overall, the weight of fruits, nuts, water and albumen of all hybrids were reduced with increasing damage of the coconut mite. Two contrasting groups of hybrids regarding the response to mite attack were formed: the first consisted of more productive hybrids, however more susceptible to mite attack (PB113, PB123, PB132) while the latter was composed of less productive hybrids, yet more tolerant to coconut mite attack (PB111, 121, 141). The hybrid PB113 was superior to the others based on fruit, nut, water and albumen weights when not attacked by the coconut mite. Although more productive, this hybrid was highly susceptible to mite attack, which can be evidenced by significant reductions in all parameters evaluated up to attack level 2. In conclusion, our results indicate the superiority of the PB113 hybrid for the conditions of Pará state based on the interaction of the hybrids with the damage caused by the coconut mite. Although this hybrid was considered susceptible to the attack of this pest, it was the most productive in terms of fruit, water, albumen, and nut weights.